Solution self-assembly of flower-like ZnO nanostructures with nanosheets and their optical properties. (2nd January 2016) - Wang, Y.; Ma, Q.; Kong, J.; Jia, H.; Wang, Z.
Abstract : A uniform flower-like ZnO materials assembled by nanosheets have been synthesised on a large scale by a facile, cost efficient and room temperature solution route without the assistance of any substrate, template or seed layers. X-ray diffraction and field emission scanning electron microscopy were employed to characterise the phase composition and morphology of the samples, and ultraviolet–visible (UV-vis) diffuse reflectance spectrum and photoluminescence (PL) spectrum were used to analyse the optical properties of the samples. The flower-like ZnO materials with an average diameter of ∼2 μm are composed of interacted nanosheets with an average thickness of ∼5 nm. A reasonable growth mechanism that the formation of this kind of flower-like ZnO structures experienced a two-stage nucleation growth process was discussed. Based on the UV-vis diffuse reflectance spectrum, the band gap of hierarchical flower-like ZnO materials was calculated to be 3·27 eV. The PL spectrum suggests that flower-like ZnO materials only emit UV light and possess good optical properties.